Dominant Factors of Adherence with Taking Medicine in Elderly Hypertensive Patients - Herlina, Herlina; Mardhiati, Retno; Pangestika, Rismawati (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Adherence to taking medication is a prerequisite for hypertension treatment to be more effective and most likely to cure patients in controlling hypertension so that complications and death do not occurObjective: The objective of this study is to discover the dominant factors of elderly hypertension patients' conformity to medication at the Jatinegara District Health CenterMethods: It is a quantitative study with Cross Sectional approach. It involved 200 respondents, as the sample was taken using a quota sampling technique.Results: Univariate results showed that 25% of elderly hypertensive patients did not adhere to medication. In bivariate analysis, it was found that family support, self-efficacy, motivation, and health workers' roles were related (p-value <0.05) to adherence to hypertension medication consumption. Meanwhile, no relation (p-value 0.05) existed between age, knowledge, attitude, access to healthcare facilities, and JKN participation variables. The dominant variable observed from the multivariate result was the interaction of attitudes and self-efficacy (OR: 23,943).Conclusion:Based on multivariate analysis, it was found that the influential factors were self-efficacy and attitudes.